A Bayesian network meta-analysis regarding the comparative efficacy of therapeutics for ALK-positive, brain metastatic non-small cell lung cancer. (December 2021) - Zhao, Binghao; Han, Yan; Wang, Yadong; Wang, Yuekun; Wang, Yaning; Xing, Hao; Dai, Congxin; Wang, Yu; Wang, Hanping; Ma, Wenbin
Abstract: More clinical evidence is needed regarding the ranking priority of interventions for ALK-positive, brain metastatic (BM) non-small cell lung cancer (NSCLC). Eligible randomized controlled trials (RCTs) were identified. Progression-free survival (PFS), objective response rate (ORR) and overall survival (OS) for the intended populations were analyzed with random effects, Bayesian network meta-analysis with the estimated hazard ratio (HR) and odds ratio (OR) with 95% credible interval (95% CrIs). We included 11 RCTs (2687 NSCLC and 991 BM patients) investigating 7 treatments and 5 medication classes. For PFS for BM patients, lorlatinib (hazard ratio (HR): 0.01, 95% CrI: 0.001–0.12), alectinib (HR: 0.05, 95% CrI: 0.01–0.21) and brigatinib (HR: 0.07, 95% CrI: 0.007–0.76) were top-ranking individual treatments; for ORR for BM patients, brigatinib, lorlatinib and alectinib were top-ranking treatments. For PFS for all NSCLC patients, the top-ranking individual treatments were lorlatinib (HR: 0.05, 95% CrI: 0.02–0.13), alectinib (HR: 0.09, 95% CrI: 0.05–0.18) and brigatinib (HR: 0.11, 95% CrI: 0.05–0.28). For OS for all NSCLC patients, we found that no individual treatments were superior to chemotherapy, whereas the following top-ranking interventions were alectinib (HR: 0.29, 95% CrI: 0.03–1.68), lorlatinib (HR: 0.41, 95% CrI: 0.04–4.13), and ceritinib (HR: 0.63, 95% CrI: 0.10–4.25). The results of individual treatments and medication classes were similar. Data were limited in regard to subgroup analyses and adverse events of BM patients. Lorlatinib has the most statistical superiority for BM patients, but ORR differences between third- and second-generation inhibitors are not obvious. All things considered, alectinib is recommended as first-line treatment, followed by lorlatinib, especially after developing drug resistance to alectinib. Graphical Abstract: ga1 Highlights: ● Lorlatinib has the most statistical superiority for BM patients. ● Alectinib was most effective among the second-generation ALK inhibitors for better penetration to the brain. ● Comprehensively, alectinib is the best upfront therapy, then sequential lorlatinib can be considered. ● Further studies are encouraged to provide mature OS results and intracranial PFS or response rates. ● Defining the best upfront TKIs and therapeutic sequences reveals an evolving area of clinical investigation.